Modeling and animating realistic faces from images - Pighin, Frederic (ProQuest Dissertations & Theses, 1999)
This dissertation addresses the problems of modeling and animating realistic faces. The general approach followed is to extract information from face photographs and videos by applying image-based modeling and rendering techniques. Given a set of face photographs taken simultaneously, our modeling technique permits us to interactively recover a 3D face model. We present animation techniques based on morphing between face models corresponding to different expressions. We demonstrate that a wide range of expressions can be generated by forming linear combinations of a small set of initial expressions. Given a video sequence, this linear face model can be used to estimate the face position, orientation, and facial expression at each frame. The thesis also explores different applications of face tracking, such as performance-driven animation and alterations of the original footage.